Strategies for Improving Organizational Efficiency, Productivity, and Performance through Technology Adoption - Jailyn Berenice Palad (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
With an emphasis on digital transformation, this thesis analyzes methods for enhancing organizational effectiveness and competitiveness through the use of technology. There is a growing need for administrators and managers to comprehend and execute digital transformation strategies due to the widespread use of technology in businesses. The research combines different techniques, such as a literature review, in-depth interviews, and a survey of the workforce at one company. According to the research's results, successful digital transformation initiatives require buy-in from the top down, a well-defined path forward, and a culture that prizes creativity and teamwork. Effective change management strategies that address employee concerns and utilize the benefits of digital technologies should also be an integral part of digital transformation strategies. The research also identifies digital transformation's enablers and inhibitors, and assesses how well digital transformation strategies boost productivity, efficiency, and performance in businesses. Researchers and practitioners in the field of management and administration can benefit from the study's valuable insights into the strategies for improving organizational efficiency, productivity, and performance through technology adoption. However, there are caveats to the research that should be taken into account. The results of this study need to be replicated in other settings and with bigger samples.